MODIFIED SINGLE ROLL FLAP APPROACH FOR SIMULTANEOUS IMPLANT PLACEMENT AND RECESSION COVERAGE - Kamen Kotsilkov (Peytchinski Publishing, 2021)
PURPOSE: This presentation demonstrates the application of the recently described modified single roll flap approach in a combined approach with the coronally advanced flap for simultaneous root coverage and implant placement with augmentation of an alveolar ridge defect. MATERIAL/METHODS: A 45 years old patient presented with complaints of teeth hypersensitivity and gum recessions as a result of an extraction of a fractured tooth.The clinical examination revealed an edentulous area in the lower right mandible, position #46, presenting a III class Siebert alveolar ridge defect, with a predominant horizontal volume insufficiency.Root exposures with caries lesions were observed on the neighboring teeth - #44, #45, #47. Usually, such a combined soft tissue and bone defects require multiple surgeries to achieve complete tissue augmentation. In this case, a new combined approach was performed, using the recently described by the author modified single roll flap and the protocol of the lateral approach of the coronally advanced flap for the lower jaw. RESULT: A complete root coverage, both bucally and approximaly, was present on the 4th month after surgery. In the edentulous area, a sufficient volume augmentation was observed with a presence of an adequate height and thickness of the peri-implant mucosa to achieve a good long term success of the implant born crown. CONCLUSION: The presented case proved the benefits of the newly described modified roll flap and the possibility this approach to be implemented in different surgical techniques, thus enlarging the indications of its application.